1998
DOI: 10.1139/v97-233
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of 2,2-dimethoxy-5,5-dimethyl- Δ3- 1,3,4- oxadiazoline studied with photoelectron spectroscopy. He(I) photoelectron spectrum of dimethoxycarbene

Abstract: Gas phase thermolysis of 2,2-dimethoxy-5,5-dimethyl-∆ 3 -1,3,4-oxadiazoline (1) in an ultraviolet photoelectron spectrometer by means of a CW CO 2 laser as directed heat source at 26 W gave a complex PE spectrum that included ionization bands belonging to acetone, tetramethoxyethylene (3), and dimethyl oxalate (4). Subtraction of the spectra of acetone, 3, and 4 from the pyrolysis spectrum of 1 left a simple PE spectrum that is attributed to dimethoxycarbene (2) along with some ethane. Becke3LYP/6-31+G* calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The energies of electrons in the -orbitals of TMeOE and TME are reflected by the corresponding (vertical) ionization potentials for which measured values are reported as 8.00 eV (TMeOE) 14 and 8.44 eV (TME). 15 Therefore, TMeOE should be somewhat more reactive than TME toward electrophilic carbenes.…”
mentioning
confidence: 99%
“…The energies of electrons in the -orbitals of TMeOE and TME are reflected by the corresponding (vertical) ionization potentials for which measured values are reported as 8.00 eV (TMeOE) 14 and 8.44 eV (TME). 15 Therefore, TMeOE should be somewhat more reactive than TME toward electrophilic carbenes.…”
mentioning
confidence: 99%
“…The PE spectra of dimethoxycarbene and methoxy(methylthio)carbene were also obtained with the laser pyrolysis technique. [207] Comparison of the SiF 4 -sensitized multiphoton CO 2 -laser pyrolysis of tetralin with the conventional flow pyrolysis at 750 o C/1 atm N 2 indicated that a significant proportion of surface-catalyzed reaction took place under the conventional conditions, leading to 1,2dihydronaphthalene and naphthalene. This was largely avoided under the laser excitation conditions, [208] where energy transfer is by collision with the bath gas.…”
Section: Gas Phase Laser Pyrolysismentioning
confidence: 99%
“…As it is well established that the correct geometry optimizations of molecules containing chalcogen atoms require the addition of d-polarization functions (19)(20)(21)(22)(23), we have used the above triple zeta split valence basis set augmented by two dpolarization functions, one p-polarization function on hydrogen atoms, as well as one diffuse function on hydrogen atoms. The interpretation of the PE spectra was based on our successfully applied method (11,24,25,26) that is basically an extension of Koopman's theorem. The simulated PE spectra of all compounds were obtained by anchoring the KohnSham MO orbital energies to the calculated first IP using our Fortran program PESPEC (12(a)).…”
Section: Experimental Detailmentioning
confidence: 99%